Traditional homemade recipes at the Versova Koli Seafood Festival - Mumbai Archive Project Team (Jio Institute, 2024)
Traditional homemade recipes take centre stage at the Versova Koli Seafood Festival, offering a taste of authenticity rarely found in restaurant food. Visitors to the festival learn about the art of Koli cooking by attending live cooking demonstrations and culinary workshops conducted by expert chefs and Koli women.